2003
DOI: 10.1023/a:1024409123726
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Topical Ceramides for Cutaneous Breast Cancer

Abstract: To our knowledge, this trial is one of the first clinical investigations of short chain ceramides. This trial's results are not promising enough to merit further study of ceramides in the manner prescribed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Topical application of ceramide to skin cancer or application of ceramide through a transarterial catheter to tumors such as hepatoma might be potential. In this context, topical treatment of refractory cutaneous breast cancer with short chain ceramide was recently reported, although the results were not promising [121].…”
Section: Clinical Application Of Ceramidementioning
confidence: 99%
“…Topical application of ceramide to skin cancer or application of ceramide through a transarterial catheter to tumors such as hepatoma might be potential. In this context, topical treatment of refractory cutaneous breast cancer with short chain ceramide was recently reported, although the results were not promising [121].…”
Section: Clinical Application Of Ceramidementioning
confidence: 99%
“…Further contribution of PS, C6-PS or ceramide III to induction of UVB-induced apoptosis which per se is partially caused by endogenous ceramide generation (19,28) could not be verified at the level of caspase-3 activity and nucleosomal fragmentation. Also in human skin in vivo, no evidence for increased apoptosis has been found in phase II topical trials for cutaneous breast cancer where a 1% mixture of C2-and C6-ceramides was ineffectual in inducing tumor cell apoptosis morphologically or by the TUNEL assay (29). Also, topical application of N-oleoyl phytosphingosine to human skin which had been barrier compromised by tape stripping and subsequently irradiated with 2MED UVB did not lead to any histological differences with regard to apoptotic cells in comparison with the vehicle-treated skin (30).…”
Section: Resultsmentioning
confidence: 99%
“…In 2003, topical administration of C 2 and C 6 ceramides were employed in a phase II study against cutaneous breast cancer, with mixed results (Clinical trial #: NCT00008320) (ClinicalTrials.gov). The trial found that while the C 2 and C 6 ceramides had little to no toxicity, patients yielded only a 4% response rate, shelving topical administration of short chain ceramides as a potential chemotherapeutic (Jatoi et al, 2003). However, by encapsulating a C 6 ceramide into stable nontoxic nanoliposomes, researchers found that they could increase chemotoxicity as compared to free ceramide alone in in vivo models (Kester et al, 2015; Sun et al, 2008).…”
Section: Deliverable and Clinically Relevantsphingolipid-based Drugs mentioning
confidence: 99%